2017
DOI: 10.7554/elife.31324
|View full text |Cite
|
Sign up to set email alerts
|

The AAA ATPase Vps4 binds ESCRT-III substrates through a repeating array of dipeptide-binding pockets

Abstract: The hexameric AAA ATPase Vps4 drives membrane fission by remodeling and disassembling ESCRT-III filaments. Building upon our earlier 4.3 Å resolution cryo-EM structure (Monroe et al., 2017), we now report a 3.2 Å structure of Vps4 bound to an ESCRT-III peptide substrate. The new structure reveals that the peptide approximates a β-strand conformation whose helical symmetry matches that of the five Vps4 subunits it contacts directly. Adjacent Vps4 subunits make equivalent interactions with successive substrate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
111
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(144 citation statements)
references
References 61 publications
(82 reference statements)
24
111
3
Order By: Relevance
“…Vps4 enzymes contain three different structural elements: ( a ) an N-terminal MIT domain that binds the tails of ESCRT-III proteins (Figures 2 c and 5 a ); ( b ) a central ATPase cassette comprising large and small domains that mediate hexamerization and ATP hydrolysis; and ( c ) a β-domain insert within the small ATPase domain that binds LIP5 (Vta1), an ATPase activator and ESCRT-III-binding protein. Our understanding of the enzyme’s structure and molecular mechanism has increased dramatically with recent high-resolution cryo-EM structures of Vps4 proteins in their active, hexameric ring conformations (Han et al 2017, Monroe et al 2017, Su et al 2017, Sun et al 2017), particularly structures of the yeast Vps4 enzyme in complex with an ESCRT-III substrate (Han et al 2017, Monroe et al 2017). These structures revealed that Vps4 forms an asymmetric ring hexamer that binds the exposed tails of ESCRT-III subunits and translocates the subunits through the constricted central pore of the hexamer.…”
Section: Vps4 and Related Aaa Atpasesmentioning
confidence: 99%
See 4 more Smart Citations
“…Vps4 enzymes contain three different structural elements: ( a ) an N-terminal MIT domain that binds the tails of ESCRT-III proteins (Figures 2 c and 5 a ); ( b ) a central ATPase cassette comprising large and small domains that mediate hexamerization and ATP hydrolysis; and ( c ) a β-domain insert within the small ATPase domain that binds LIP5 (Vta1), an ATPase activator and ESCRT-III-binding protein. Our understanding of the enzyme’s structure and molecular mechanism has increased dramatically with recent high-resolution cryo-EM structures of Vps4 proteins in their active, hexameric ring conformations (Han et al 2017, Monroe et al 2017, Su et al 2017, Sun et al 2017), particularly structures of the yeast Vps4 enzyme in complex with an ESCRT-III substrate (Han et al 2017, Monroe et al 2017). These structures revealed that Vps4 forms an asymmetric ring hexamer that binds the exposed tails of ESCRT-III subunits and translocates the subunits through the constricted central pore of the hexamer.…”
Section: Vps4 and Related Aaa Atpasesmentioning
confidence: 99%
“…The E subunit is displaced slightly from its idealized helix position, and the sixth (F) Vps4 subunit sits outside the helix and is fully disengaged from the substrate (Figure 5). The nucleotide state of each subunit in the active hexamer has not been determined with absolute certainty, but it appears that subunits A–C bind ADP•BeF x in an ATP-like configuration and D and E bind ADP, while the F subunit appears to lack a nucleotide (Han et al 2017). Nucleotides bind at subunit interfaces and are canonically coordinated by ( a ) a Walker A motif, which contacts the adenosine base, sugar, and first two phosphates; ( b ) a Walker B motif, which chelates a magnesium ion and catalytic water; and ( c ) two arginine finger residues from an adjacent subunit, which coordinate the gamma phosphate and help promote ATP hydrolysis (Wendler et al 2012).…”
Section: Vps4 and Related Aaa Atpasesmentioning
confidence: 99%
See 3 more Smart Citations